2007
DOI: 10.1002/elps.200700129
|View full text |Cite
|
Sign up to set email alerts
|

Determination of glyoxal and methylglyoxal in the serum of diabetic patients by MEKC using stilbenediamine as derivatizing reagent

Abstract: An analytical method has been developed for the separation of glyoxal (Go), methylglyoxal (MGo), and dimethylglyoxal (DMGo) by MEKC using stilbenediamine (SD) as derivatizing reagent, separation time 6.5 min, SDS as micellar medium at pH 8, and sodium tetraborate (0.1 M) as buffer. Uncoated fused-silica capillary, effective length 50 cm x 75 microm id; applied voltage 20 kV and photodiode array detection, were used. Calibration was linear within 0.02-150 microg/mL with detection limits 3.5-5.8 ng/mL. Go and MG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…However, it is not clear how MG moves across cellular membranes (29). The plasma MG level is 2 μM in diabetic patients, whereas it is approximately 0.6 μM in nondiabetic subjects (30,31). Although MG concentrations used in our experiments were much higher than the plasma MG level, it is possible that MG incorporated into cells acts at physiologically relevant levels.…”
Section: Discussionmentioning
confidence: 77%
“…However, it is not clear how MG moves across cellular membranes (29). The plasma MG level is 2 μM in diabetic patients, whereas it is approximately 0.6 μM in nondiabetic subjects (30,31). Although MG concentrations used in our experiments were much higher than the plasma MG level, it is possible that MG incorporated into cells acts at physiologically relevant levels.…”
Section: Discussionmentioning
confidence: 77%
“…Two experimental limitations should be discussed. First, the MG concentration present in the culture medium is much higher than that found in diabetic patient plasma (31,35). However, it must be indicated that clinical situations are much more complicated, and actual MG concentrations to which in vivo cells are exposed remain uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…However, analytical investigations were often limited to few selected compounds like glyoxal, methylglyoxal and 3-DG [5,12,[79][80][81][82][83][84][85]. A more comprehensive approach including important intermediates from a mechanistic point of view is needed, e.g.…”
Section: Relevance In Vivomentioning
confidence: 99%